STUDY VACUUM AND NON VACUUM PACKAGING ON THE QUALITY OF FISH BALLS MALONG (Muarenesox talabon) DURING COLD STORAGE TEMPERATURE (±50C) - Zainuddin Nasution; Mirna Ilza; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
A Study vacuum and non vacuum packaging on the quality of fish balls malong (Muarenesox talabon) during cold storage temperature (±50C), has been carried out in June-July 2016. This research aim to understand the different of vacuum and non vacuum packaging on the quality of fish balls malong (Muarenesox talabon) during cold storage temperature (±50). The method used is an experimental method that perform method processing comperative malong fish balls are packed in a vacuum and non vacuum during cold storage temperature (±50C). The treatment in this study is a vacuum and non vacuum packaging. Meanwhile, as replication is the shelf life of 0,7,14,21 and 28 days, with the number of experimental units is 7 units. Parameter test in the organoleptic (appearance, aroma, flavour, and texture), chemical analysis (water and fat), and analysis of total plate count test (TPC). Furthermore, the data were analyzed using t-test. Treatment of the best views of the organoleptic test are on treatment with a value of such a vacuum packaging appearance value (5,55), aroma (5,11), flavour (4,66), texture (5,68), with a water content (59,13%), fat content (2,31%), ( TPC 5,20 cfu/gram).Keywors: Meatball, Muarenesox talabon, vacum package and non vacum package, quality